Fcµ Receptor Promotes the Survival and Activation of Marginal Zone B Cells and Protects Mice against Bacterial Sepsis - Liu, Jun; Zhu, Hanying; Qian, Jiawen; Xiong, Ermeng; Zhang, Lumin; Wang, Yan-Qing; Chu, Yiwei; Kubagawa, Hiromi; Tsubata, Takeshi; Wang, Ji-Yang (Frontiers in Immunology, 2018)
The marginal zone B cells (MZB) are located at the interface between the circulation and lymphoid tissue and as a gatekeeper play important roles in both innate and adaptive immune responses. We have previously found that MZB are significantly reduced in mice deficient in the IgM Fc receptor (FcμR) but how FcμR regulates the development and function of MZB remains unknown. In the present study, we found that both marginal zone precursor (MZP) and MZB were decreased in FcμR-/- mice. The reduction of MZP and MZB was not due to impaired proliferation of these cells but rather due to their increased death. Further analysis revealed that FcμR-/- MZB had reduced tonic BCR signal, as evidenced by their decreased levels of phosphorylated SYK and AKT relative to WT MZB. MZB in FcμR-/- mice responded poorly to LPS in vivo as compared to MZB in WT mice. Consistent with the reduced proportion of MZB and their impaired response to LPS, antibody production against the type 1 T-independent Ag, NP-LPS, was significantly reduced in FcμR-/- mice. Moreover, FcμR-/- mice were highly susceptible to Citrobacter rodentium-induced sepsis. These results reveal a critical role for FcμR in the survival and activation of MZB and in protection against acute bacterial infection.